Peningkatan Motivasi Belajar Bahasa Inggris Melalui Metode Total Physical Response (TRP) Pada Siswa Kelas VII MTSN 9 Kampar - Yenni, Syasri (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
This research was conducted in three cycles. In order for this classroom action research to work well without obstacles that interfere with the smooth running of the research, the researcher compiled the stages that were passed in the classroom action research, namely: 1) Action planning/preparation, 2) Action implementation, 3) Observation, and 4) Reflection. Learning using the Total Physical Response (TPR) method can increase student motivation in learning English. The use of the Total Physical Response (TPR) method can turn students into active learners, relieve stress on students and teachers and provide motivation that learning English is easy. It can be proven by the results of student learning in cycle III there was an increase in mastery from 24 students or 49% to 45 students or 92%, an increase of 21 students or 43% of the total 49 students. Thus, the Total Physical Response method can spur students to be more active in understanding and mastering colors material. This is evidenced from the results of the analysis obtained, that the value of student learning outcomes increases and students are more enthusiastic about learning English from cycle I to cycle III. This increased motivation and student learning outcomes achieved is proof that students have succeeded in mastering the material by 75-100%